THE EXISTENCE OF ISLAMIC BOARDING SCHOOLS IN INCREASING THE POTENTIAL AND COMPETITIVENESS OF STUDENTS TOWARDS A GOLDEN INDONESIA 2045 - Asy’ari, Asy’ari; Makalao, Dwi Ajeng Maulidya; Yusuf, Ilham Agustian Widia; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study analyzes the role of Islamic boarding schools (pesantren) in enhancing the potential and competitiveness of students (santri) to support the vision of Golden Indonesia 2045. Using a qualitative approach and a case study at Mazro'atul Ulum Islamic Boarding School, the research explores how an inclusive and adaptive curriculum, as well as interactions between santri and non-santri, contribute to shaping an inclusive and competitive social identity. The findings show that the diverse social environment in pesantren influences the curriculum and teaching methods to meet the needs of both santri and non-santri. The use of modern technology in learning also supports santri's digital skills relevant in the global era. The pesantren’s involvement in social activities strengthens the relationship between pesantren and the surrounding community, fostering constructive social harmony. These findings indicate that pesantren can become educational centers that produce highly competitive generations with a global outlook, while remaining firmly rooted in traditional values, in line with the goals of Golden Indonesia 2045